2014
DOI: 10.3855/jidc.3495
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of fluoroquinolone-resistant Salmonella enterica serovar Kentucky from poultry and poultry sources in Nigeria

Abstract: Introduction: This study investigated the antimicrobial resistance and clonality of Salmonella enterica serotype Kentucky in poultry and poultry sources in Nigeria, and compared the isolates with the clone of S. Kentucky STI98-X1 CIP R using (PFGE) and (MIC). Methodology: Fecal samples from chickens and poultry sources (litter, water, rodent and lizard fecal samples) were collected from fourteen (14) poultry farms in 2007, 2010 and 2011 and were analyzed for S. Kentucky. Results and conclusions: Six percent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 13 publications
(18 reference statements)
1
27
0
Order By: Relevance
“…This category included 42 studies, with the inclusive eligibility criteria in which diverse phenotypic or genotypic methods were utilized ([14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55], Tables S1–S3). These studies sought to detect the presence and extent of AMR in collected samples with a selected panel of antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This category included 42 studies, with the inclusive eligibility criteria in which diverse phenotypic or genotypic methods were utilized ([14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55], Tables S1–S3). These studies sought to detect the presence and extent of AMR in collected samples with a selected panel of antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…The 80 studies excluded did not directly relate to the objectives or yielded information that could be subjected to organized peer review and data analysis. The 59 included studies were sorted into three categories of 42 antimicrobial resistance studies [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55], 16 antimicrobial residue studies [56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71], and 1 antiseptic or disinfectants study [72]. The PRISMA-style flowchart was modified and used for this analytical review (Figure S1) [73].…”
Section: Methodsmentioning
confidence: 99%
“…One isolate was typed as ST314, which to‐date is a relatively rare ST in the United States, but has been isolated from pet reptiles in Poland, humans and poultry in the United Kingdom and Africa, and cattle in the Middle East (Alikhan et al, ; Zając et al, ). Nine isolates were typed as ST198, which has been isolated from individuals travelling from Africa, the Middle East, Europe and South Asia, and is frequently isolated from poultry and cows, in these regions, and occasionally isolated from cows, ground beef and poultry products in the United States (Albert et al, ; Haley et al, ; Hello, Bekhit et al, ; Hello, Harrois et al, ; Le Hello et al, ; Mulvey et al, ; Raufu et al, ; Weill et al, ). Of these nine ST198, five were isolated from individuals reporting recent international travel to regions where travel‐associated S .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the available data in the S. enterica multilocus sequence type (MLST) database, two sequence types (ST), ST152 and ST198, are among the most frequently isolated and characterized of the known S. Kentucky STs (Alikhan, Zhou, Sergeant, & Achtman, ). ST152 is typically associated with poultry and dairy cows in the United States, and ST198 is typically associated with human infections acquired in Africa, South Asia, the Middle East and Europe, as well as poultry and cattle in these regions (Foley et al, ; Haley et al, ,; Le Hello et al, ; Raufu et al, ). However, the geographic distinction between these types is not perfect as ST152 has been isolated outside of the Americas and ST198 has been isolated in the Americas (Alikhan et al, ; Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…41 A Greek study on E. coli found in meat from retail stores showed that isolates from chicken had higher levels of resistance to ciprofloxacin (62.5%) than those in lamb/goat isolates, 42 which in turn were higher than those in beef isolates (27.9%). 43 Related studies on the prevalence of resistant pathogens in retail raw poultry in China are described by Yang et al, 44 in Italy by Giacomelli et al,45 in Nigeria by Raufu et al,46 in the United Kingdom by McNeece et al, 47 and in Vietnam by Ta et al 48 It is noteworthy that Sapkota et al 49,50 observed lower levels of resistant bacteria in poultry farms in the United States that transitioned to organic practices without the use of antibiotics. A review of the literature by Smith-Spangler et al 51 indicates that the risk of isolating bacteria resistant to three or more antibiotics was higher in conventional than in organic chicken or pork (risk difference 33%).…”
Section: Bacteria In the Food Chainmentioning
confidence: 93%